Family Communication Patterns and Children’s Influence on Purchase Decisions - Sharma, Adya; Sonwaney, Vandana (Indian Journal of Marketing, 2015)
Traditionally, children were not viewed as consumers. They were perceived as learners who learnt from various socialization agents how to become consumers. The social, cultural, and economic changes in the past few decades have redefined the role of children in family purchase decisions. Children’s influence on purchase decisions has been acknowledged by the research fraternity. The paper specifically explored the effect of family communication patterns on children’s influence on purchase decisions. Through hierarchical regression, empirical findings were presented.